Pubertal timing and health-related behaviours in adolescence - socio- economic outcomes in a follow-up study from Finland (Italian Journal of Public Health, 2006)
Background. Pubertal timing is connected with health-related lifestyle in adulthood. We studied whether early or late pubertal timing is predictive of socio-economic outcomes in early adulthood and whether the associations are mediated by health behaviours.Methods. Survey data (1981, 1983, 1985, 1987) from samples of 14-year-old Finns (N=4246, response rate 85%) were linked with respondents’ attained educational level, socio-economic and labour market position in 2001 (ages 28-34). Ages of menarche and first ejaculation indicated pubertal timing.Results. As compared to adolescents with average age pubertal timing, boys and girls maturing at an early age more often participated in health-compromising behaviours, while those maturing at a later age participated less frequently. Pubertal timing was not associated with attained educational level or socioeconomic position in girls and not with labour market position at the time of follow-up in either sex. In boys, independently of health behaviours, early or late onset of puberty predicted low educational level, while late onset predicted low socio-economic position.Conclusion. Timing of puberty has a stronger connection with socio-economic outcomes in boys than in girls. Deviance from the normative pace of physical development, especially late maturation, is among boys slightly depicted in the hierarchy of socio-economic positions of the society. As pubertal timing is connected with health-related behaviours – especially with smoking – the pacing of developmental transitions should be considered in planning programmes preventing unhealthy behavioural patterns often linked with negative attitudes towards schooling.
Keywords: Pubertal timing; health behaviours; educational level; socio-economic position; labour market position